The Role of RNA-Binding Protein HuR in Lung Cancer by RNA Sequencing Analysis - Ye, Xiong; Fu, Qiang; Xiao, Hui (Frontiers in Genetics, 2022)
Background The overexpression of human antigen R (HuR) has been proven in various types of cancer and is associated with the poor survival lung cancer patients. HuR overexpression stabilizes the mRNA of tumor-promoting genes by binding with 3'-UTR AU-rich elements (ARE). However, the role of HuR in the proliferation of lung cancer is unclear. Methods HuR expression was assessed using immu¬nohistochemistry of tumor tissue samples from ten patients with lung cancer and ten patients with benign lung disease. Gene, protein, mRNA, and lncRNA changes in A549 HuR knockdown (KD) cells were assessed by single-cell RNA sequencing analysis. Furthermore, cell proliferation, migration, and invasion were determined by Cell Counting Kit-8 (CCK-8) assays and Transwell assays with or without Matrigel. The cell cycle was assessed by propidium iodide (PI) staining. The protein level, mRNA level and half-life of PLK1 were detected by western blotting and RT-qPCR. Results In clinical patients, the expression of HuR was significantly higher in lung cancer patients than in patients with benign lung disease. RNA sequencing analysis of A549 HuR KD cells revealed that the main function of HuR was related to ribonucleoprotein complex biogenesis. HuR was found to regulate signaling pathways mainly related to the spliceosome, RNA transport and the cell cycle. HuR KD suppressed the proliferation, migration and invasion of A549 cells, indicating its promotive role in these processes. Conclusion These results demonstrate that HuR plays an important role in the progression of lung cancer.